A study of affect in slices and support parameters on dimensional accuracy for FDM prototype - Salleh, Ahmad Faizal; Mohammad Khan, Shah Fenner Khan; Sharif, Safian; Mohamad, Zulkepli; A. Rashid, Zulkifli; Murad, Muhamad Nasir (2006)
Rapid prototyping process enables creation of complex physical components in relatively shorter building time and wide materials utilization. Fused deposition modeling, often referred FDM, is a type of rapid prototyping (RP) technology commonly used within engineering design and manufacturing environment. FOM works on an "additive" principle by laying own material in layers. 3D models are translated into .STL file to be used in FDM machine. The model is built up from layers the plastic hardens immediately after extrusion from the , nozzle. The data preparation process in the FDM machine prior , prototype building involves lot of parameters setting. The ffect of these parameters on the product needs to be evaluated or obtaining product with optimum quality. This project study e effect of slice thickness and support parameters on the Water , luble System, Fused Deposition Modeling (FDM) product i~ality in terms of dimensional accuracy produced during part ~uilding. The results obtained show that considered parameters fluence the studied responses. The influences on the angular imensional accuracies are higher as compare to the linear dimensions. Future work studies are being conducted to hance the knowledge in understanding parameters setting that canbe utilized to produce better quality product.